Global perspectives on social media in tertiary learning and teaching emerging research and opportunities - Piven, Inna 1971-; Gandell, Robyn 1959-; Lee, Maryann 1971-; Simpson, Ann M. (IGI Global, Disseminator of Knowledge, 2018)
"This book reviews important concepts, possible pedagogies and potential educational contexts related to social media use in the higher education classroom. It also looks at the evolving nature of the technologies and practices available in today's teaching and learning context as well as ones that are considered to impact higher educational learning and teaching in the future" ...
Includes bibliographical references
Keywords: Social media in education -- New Zealand; Internet in higher education -- New Zealand; Education, Higher -- Effect of technological innovations on -- New Zealand